Improvement of grinding performance in ultra-precision grinding of lens mould by the help of megasonic coolant. (7th June 2006) - Tanaka, Katsutoshi; Fukuta, Masahiko; Suzuki, Kiyoshi; Iwai, Manabu; Uematsu, Tetsutaro; Mishiro, Syoji
In order to eliminate the difficulty in machining a tungsten carbide glass lens mould by using a fine diamond wheel, a new type of coolant supply method – the megasonic coolant supply method – is introduced. Using the megasonic coolant supply method, a substantial reduction in the error factor presently associated with the grinding wheel can be achieved, thus making it possible to achieve the target accuracy without using any compensation parameters. Increased wheel life and increased depth of cut have also been achieved along with an improvement in the machined surface quality.